2020
DOI: 10.1101/2020.04.17.047548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Structural Flexibility within SARS-CoV-2 Spike Protein Reveals Potential Therapeutic Targets

Abstract: The emergence and rapid worldwide spread of the novel coronavirus disease, COVID-19, has prompted concerted efforts to find successful treatments. The causative virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), uses its spike (S) protein to gain entry into host cells. Therefore, the S protein presents a viable target to develop a directed therapy. Here, we deployed an integrated artificial intelligence with molecular dynamics simulation approach to provide new details of the S protein struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The trimer-binding interface between individual S protomers and the interaction sites of trimerization are not fully characterized for the SARS-CoV-2. Recent studies have suggested several residues that contribute to the formation or to stabilize the S trimeric structure; and most of them are located at the S2 subunit (mainly in the S2-NTD, FP, CR, HR1, CH and CD) [53] , [54] , [55] , [56] , [57] , [58] . Thirteen of these residues (E702, Y707, N709, N710, Y789, K790, K795, F797, G798, T859, G891, Q895, F898) are described by multiple authors and represent CDR or T-RHS for drug targeting highlighted in our study [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Resultsmentioning
confidence: 99%
“…The trimer-binding interface between individual S protomers and the interaction sites of trimerization are not fully characterized for the SARS-CoV-2. Recent studies have suggested several residues that contribute to the formation or to stabilize the S trimeric structure; and most of them are located at the S2 subunit (mainly in the S2-NTD, FP, CR, HR1, CH and CD) [53] , [54] , [55] , [56] , [57] , [58] . Thirteen of these residues (E702, Y707, N709, N710, Y789, K790, K795, F797, G798, T859, G891, Q895, F898) are described by multiple authors and represent CDR or T-RHS for drug targeting highlighted in our study [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Resultsmentioning
confidence: 99%
“…Two recent preliminary molecular dynamics studies shifted the focus to the S2 subunit protein of the heterodimer (protomer of the S trimer). In the first study, two regions in the S2 subunit of the dimer and the hinge connecting the S1 and S2 subunits were identified (12). In the second study, the S2 subunit was found to exhibit much less variability and flexibility than the RBD domain in the S1 subunit (48).…”
Section: Figurementioning
confidence: 99%
“…The Convolutional Variational Autoencoder or CVAE was used for analysis, 40 which has been optimized for large scale systems on HPC platform. 71 The implementation of CVAE has been previously shown to provide meaningful insights to diverse systems such as protein folding, 72 enzyme dynamics, 41,73 Coronavirus spike protein 74 and Coronavirus non-structured proteins. 75 A CVAE consists of a variational autoencoder along with multiple convolutional layers.…”
Section: Cvae-based Deep Learning Implementationmentioning
confidence: 99%